Advances in liquid crystalline nano-carbon materials: preparation of nano-carbon based lyotropic liquid crystal and their fabrication of nano-carbon fibers with liquid crystalline spinning - Choi, Yong-Mun; Jung, Jin; Hwang, Jun Yeon; Kim, Seung Min; Jeong, Hyeonsu; Ku, Bon-Cheol; Goh, Munju (한국탄소학회, 2015)
This review presents current progress in the preparation methods of liquid crystalline nano-carbon materials and the liquid crystalline spinning method for producing nano-carbon fibers. In particular, we focus on the fabrication of liquid crystalline carbon nanotubes by spinning from superacids, and the continuous production of macroscopic fiber from liquid crystalline graphene oxide.